1989
DOI: 10.1021/bi00434a030
|View full text |Cite
|
Sign up to set email alerts
|

Conformation and dynamics of a left-handed Z-DNA hairpin: studies of d(CGCGCGTTTTCGCGCG) in solution

Abstract: The physical properties of the DNA oligomer d(CGCGCGTTTTCGCGCG) in solvents containing 4 M NaClO4 and 0.1 M NaCl were investigated by proton NMR, optical melting, and circular dichroism spectroscopy. Results of these investigations are as follows: (i) The DNA hexadecamer exists as a unimolecular hairpin in either high or low salt. (ii) In high salt the stem region of the hairpin is in the left-handed Z conformation. (iii) In either high or low salt, the duplex stem of the hairpin is stabilized against melting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 50 publications
2
34
0
Order By: Relevance
“…The main results of this series of investigations can be briefly described as follows: In all cases the presence of the tetraloop leads to a considerable increase of thermal stability compared to that measured in a reference double helix containing the same base repeat as in the stem of hairpins. As previously mentioned,40 the added stability of the hairpin is of entropic origin. Based on UV and NMR results,37 the stem of d(CG) 5 T 4 (CG) 5 hairpin undergoes a B‐to‐Z formtransition in particular conditions: high concentration of Na + or Mg 2+ and dehydration (ethanol) conditions. NMR results have shown that the oligomer d(CG) 2 T 4 (CG) 2 forms a tetraloop hairpin with a B form stem 38. The use of distance geometry calculations have permitted the obtention of the T 4 tetraloop hairpin three‐dimensional (3D) structure (up to now the only existing structural model of this hairpin in solution).…”
Section: Introductionmentioning
confidence: 67%
See 2 more Smart Citations
“…The main results of this series of investigations can be briefly described as follows: In all cases the presence of the tetraloop leads to a considerable increase of thermal stability compared to that measured in a reference double helix containing the same base repeat as in the stem of hairpins. As previously mentioned,40 the added stability of the hairpin is of entropic origin. Based on UV and NMR results,37 the stem of d(CG) 5 T 4 (CG) 5 hairpin undergoes a B‐to‐Z formtransition in particular conditions: high concentration of Na + or Mg 2+ and dehydration (ethanol) conditions. NMR results have shown that the oligomer d(CG) 2 T 4 (CG) 2 forms a tetraloop hairpin with a B form stem 38. The use of distance geometry calculations have permitted the obtention of the T 4 tetraloop hairpin three‐dimensional (3D) structure (up to now the only existing structural model of this hairpin in solution).…”
Section: Introductionmentioning
confidence: 67%
“…The choice of the ‐TTTT‐ (hereafter referred to as T 4 ) tetraloop is related to the fact that it is one of the most documented and perhaps the unique one for which we find a substantial amount of thermodynamic and structural data in the literature 35–42. The analysis of the T 4 tetraloop hairpin was started by a systematic optical analysis of d(ATCCTA‐T n ‐TAGGAT) oligomers,35 with n = 1–5 35, 36.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, previous studies [9] utilized polyd(CG) to determine the a¤nity of ZK to Z-DNA. The two d(CG) 3 strands of this hairpin were tethered through a T 4 loop, which increases the melting temperature by 40³C ensuring that a stable duplex stem is present at room temperature [19]. Analytical ultracentrifugation veri¢ed that d(CG) 3 T 4 (CG) 3 shows the molecular weight of a hairpin (measured: 4850, theoretical: 4864) rather than that of higher molecular weight duplexes with T 4 bulges.…”
Section: Resultsmentioning
confidence: 99%
“…The Z-RNA, in particular, revealed many interesting facets about the capacity of our force field to recapitulate the heterogeneity of folded RNA motifs. The presence of an alternating purine-pyrimidine sequence and high salt concentration has been established as a prerequisite for Z-form backbones for both DNA (37) and RNA (5); additional studies of DNA tetraloops have shown B-to Z-backbone transitions in high salt concentrations (5 M NaCl) (38,39), and combinations of pressure and salt (6 kbar; 5 M NaCl) (46) have been shown to induce A to Z transitions in r(CG) 6 duplexes. From our analyses, pressure is suggested to be a destabilizing factor in the formation of Z-RNA; however, high local density of counterions clearly stabilizes Z-RNA, which was indicated by consistent ion association in increased pressure and consistent coordination within the stem minor groove.…”
Section: Discussionmentioning
confidence: 99%